Pemeringkatan Kinerja Dosen pada Perguruan Tinggi Swasta Menggunakan Algoritma Simple Additive Weighting - Mufida, Elly; Iriadi, Nandang; Andriansyah, Doni (JISKA (Jurnal Informatika Sunan Kalijaga), 2024)
The Tri Dharma of Higher Education is an obligation for lecturers while carrying out their duties as lecturers at higher education institutions, the implementation of which is regulated in Law Number 20 of 2003 concerning the National Education System. The Tri Dharma of Higher Education is a lecturer's obligation, including Education and Teaching, Research and Development, and Community Service. Lecturers need Support and motivation to implement quality Tri Dharma, especially at "X" Private Universities. Providing rewards or awards can motivate lecturers to give their best performance to Tri Dharma. Student feedback is also needed as evaluation material for lecturers to measure their teaching abilities. Rewarding lecturers can be done by ranking lecturer performance, especially at private universities. The SAW (Simple Additive Weighting) algorithm ranks lecturer performance through the criteria of education and teaching, research, community service, and student feedback. An assessment of several subcriteria presents each criterion. The normalized scoring matrix is ​​the ranking preference. From the results of data processing on lecturer performance and feedback from students, with a sample of 25 lecturers, a ranking score was obtained on a scale of 0 to 1, where a score of 1 is the highest ranking. The lecturer performance ranking process involves lecturers, students, and the Study Program Management Unit. A lecturer performance rating information system is needed to facilitate all actors' involvement in the lecturer performance rating process and provide valid and timely rating results to stakeholders.